Attitude to professional ethics in medicine postgraduate students of a medical school - Izaguirre, Manuel (2020)
Introduction. The medical profession has ceased to be respected by society as a consequence of the unprofessional behavior of many of its members, due to dehumanization, corruption and the reification of medicine by prioritizing the economic and personal well-being over the social. Objective. To know the attitude towards professional ethics in postgraduate students of the Faculty of Medicine of the Universidad Nacional Mayor de San Marcos. Methods. A descriptive, cross sectional study with a quantitative approach was carried out, using the scale of attitudes on professional ethics as an instrument. Results. The attitude towards professional ethics was positive in 81,5% and indifferent in 18,5%. The positive attitude towards professional ethics in cognitive and technical, social, ethical, and emotional-emotional competencies was 88,8%, 69,2%, 80%, and 87,7%, respectively. Conclusion. The attitude towards professional ethics was positive in 81,5% and indifferent in 18,5%.